2018
DOI: 10.1080/07391102.2018.1441073
|View full text |Cite
|
Sign up to set email alerts
|

Binding site identification of anticancer drug gefitinib to HSA and DNA in the presence of five different probes

Abstract: This study was carried out to evaluate the binding interaction of gefitinib (GEF) with human serum albumin (HSA) and calf thymus DNA (ct-DNA) using fluorescence, UV-Visible, zeta potential measurements and molecular docking methods in order to understand its pharmacokinetic mechanism. By increasing the temperature, a steady decrease in Stern-Volmer quenching constants was observed for HSA binding properties; this indicates a static type of fluorescence quenching. Negative values were calculated for Gibbs free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Small molecules interacting with DNA can be categorized as an intercalator (ligand) and groove (DNA) binders. Studies identified that gefitinib targets the EGFR receptor which is protein in nature, but it also interacts with DNA that too specifically at A‐T region of the DNA . So to check the DNA interaction properties of newly synthesized compounds absorption titrations with calf thymus (CT) DNA was piloted which is a universally used method.…”
Section: Resultsmentioning
confidence: 99%
“…Small molecules interacting with DNA can be categorized as an intercalator (ligand) and groove (DNA) binders. Studies identified that gefitinib targets the EGFR receptor which is protein in nature, but it also interacts with DNA that too specifically at A‐T region of the DNA . So to check the DNA interaction properties of newly synthesized compounds absorption titrations with calf thymus (CT) DNA was piloted which is a universally used method.…”
Section: Resultsmentioning
confidence: 99%
“…They are recognized as sensitive probes for observing DNA structure, providing affinity for site-specificity in molecular biology and yielding important properties for drug design and therapeutic potential in controlling the gene expression. [34][35][36][37][38][39][40][41][42][43] The interaction of biological entities such as ribonucleic acid (RNA), deoxyribonucleic acid (DNA), and protein with the ligand is a prominent area of exploration in developing biomedical significance. [39,[44][45][46][47][48][49][50] DNA acts as an important part of storing the genetic information that is the potential therapeutic target in cancer and various other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative stress caused by these free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species, as toxic reagents to nerve cells, destroys and disrupts their function and plays a key role in the pathological processes of several neurological disorders, such as MS and Alzheimer's disease . On the other hand, cells, by employing antioxidant machinery, could protect themselves against ROS‐induced damage and return the overall ROS levels to the equilibrium . In various pathological conditions, however, alterations in the ROS balance, due to either decreased antioxidant protection or an increase in ROS generation, result in the subsequent damage to the macromolecules comprising deoxyribonucleic acid (DNA), proteins, and lipids .…”
Section: Introductionmentioning
confidence: 99%